Chemical microscopy and nanoscopy of bio-materials and living cells, IRMMW-THz - KOPF, ILONA (IEEE, 2010)
Raman microspectroscopy of human sperm cells and nearfield infrared microscopy of nanoscale biomaterials like nanografted DNA have been performed. A newly developed station for the ANKA-IR2 beamline combines several techniques to study the same sample at the same position.
Proceedings of the 35th International Conference on Infrared Millimeter and Terahertz Waves
35th International Conference on Infrared Millimeter and Terahertz Waves (IRMMW-THz), 2010
PUBLISHED
Keywords: Biochemistry; Raman microspectroscopy; human sperm cells